2012
DOI: 10.5194/angeo-30-1015-2012
|View full text |Cite
|
Sign up to set email alerts
|

Topological skeleton of the 2-D slightly non-ideal MHD system close to X-type magnetic null points – an analysis of the general solution for the generic case

Abstract: Abstract. The appearance of eruptive space plasma processes, e.g. in eruptive flares as observed in the solar atmosphere, is usually assumed to be caused by magnetic reconnection, often connected with singular points of the magnetic field.We are interested in the general relation between the eigenvalues of the Jacobians of the plasma velocity and the magnetic field and their relation to the shape of a spatially varying, localized non-idealness or resistivity, i.e. we are searching for the general solution. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Our topological considerations revealed that the resistivity surface is a hyperbolic paraboloid, meaning that the resistivity has a saddle-point structure in the vicinity of the magnetic cusp rather than a maximum of the resistivity like in the case of a regular structurally stable magnetic X-point (Nickeler et al 2012).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Our topological considerations revealed that the resistivity surface is a hyperbolic paraboloid, meaning that the resistivity has a saddle-point structure in the vicinity of the magnetic cusp rather than a maximum of the resistivity like in the case of a regular structurally stable magnetic X-point (Nickeler et al 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Magnetic reconnection is a key process for understanding magnetic structures and their topological change in astrophysical plasmas. Many investigations analyzing especially topological or geometrical properties of physical fields, focusing either on some or involving all of them, have been done in various contexts and approaches: for example resistive magnetohydrodynamics (MHD) in 2 dimensions (2D) (Priest & Cowley 1975), kinematic ideal MHD in 3D (Lau & Finn 1990), purely magnetically in 2D and 3D (Parnell et al 1996), resistive MHD in 3D with constant resistivity (Titov & Hornig 2000), resistive MHD in 3D with locally varying but prescribed resistivity (Hornig & Priest 2003;Priest & Pontin 2009), Hall-MHD in 2.5D (Litvinenko 2009), resistive, kinematic MHD in 3D with varying resistivity (Wyper & Jain 2011), and resistive MHD in 2D with localized but consistent resistivity (Nickeler et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations